"My dog and I, we need the park": more-than-human agency and the emergence of dog parks in Poland, 2015–2020. (July 2021) - Włodarczyk, Justyna
The article analyzes the emergence of dog parks in Polandi, on the basis of stories from local media, with emphasis on how dog park proponents justify the need for establishing dog runs. Even though official arguments present dog parks as an amenity that offers training opportunities for dogs, the guardians' activism is motivated by the recognition of their dogs' needs for off-leash play and social interaction with others dogs. The guardians often phrase the arguments using language that presents the interests of the human and the canine as inseparable, sometimes even merging the human and the dog through the use of second person plural. The article identifies this type of argumentation as an expression of more-than-human agency: the humans not only see themselves as speaking on behalf of their dogs, but see themselves as speaking with their dogs. However, the article also identifies social and cultural factors that have made dog parks a desirable amenity in Poland. These include the parks' associations with progress, modernity and broadly understood "Western" culture. The drive to build parks is thus also tied with the desire for a spatial emblem of the recognition of the human-canine bond. These social and cultural factors also shape the hybrid agency at work in the Polish dog park debates.